Analisis Pengendalian Sedimentasi yang Masuk pada Sistem Kolam Retensi Danau Cimpago Padang - Muhammad Bima Dwitama Bima; Totoh Andayono; Yaumal Arbi; Risky Indra Utama (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Silting due to sedimentation is one of the problems that threatens the effectiveness of the Cimpago Padang Lake Retention Pond function as a flood control in coastal urban areas. This study aims to analyze the sedimentation rate in the retention pond system and determine alternative sedimentation control measures to maintain the pond's capacity and performance. The study used a field observation method by taking water samples from the surface, middle, and bottom layers of the pond. A total of 10 samples were analyzed at the Hydrology Laboratory of the Department of Civil Engineering, Faculty of Engineering, Padang State University using Total Suspended Solids (TSS) parameters to identify sediment distribution characteristics. The results showed that the average TSS value increased with increasing depth, namely 77.4 NTU in the surface layer, 225.5 NTU in the middle layer, and 486.6 NTU in the bottom layer. This finding indicates the occurrence of intensive sediment deposition at the bottom of the pond which has the potential to reduce the capacity and reduce the effectiveness of flood control. Therefore, sedimentation control through the construction of sediment traps, periodic dredging, management of sluice gates, and reduction of sediment sources from the water catchment area needs to be implemented to maintain the sustainability of the Cimpago Padang Lake Retention Pond function.